Peran Pendidikan Agama Islam Dalam Membangun Ketahanan Nasional Di Era Globalisasi : Sebuah Perspektif Strategis - Reza Noprial Lubis (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This article examines the strategic role of Islamic Religious Education (PAI) in strengthening Indonesia's national resilience amidst the complex challenges of globalization. Globalization brings widespread impacts, such as cultural value degradation, identity crises, and the potential for social disintegration. PAI holds an important position as a bastion of spiritual and moral values that shape the character of students to be faithful, tolerant, patriotic, and resilient in facing change. This research uses a descriptive qualitative approach based on literature study. The study results show that PAI not only functions as religious education but also as a strategic instrument in national character building, strengthening integrity, and internalizing national values. In facing structural, cultural, and human resource challenges, curriculum revitalization, integration of Islamic values into all disciplines, and optimization of educational technology utilization are necessary. The contribution of PAI is also evident in the formation of militant, spiritual, and nationalist character, as well as in maintaining an adaptive education system based on Islamic values. Thus, PAI plays a vital role in building the foundation of a resilient, inclusive, and competitive society in the global era.